VARIETY OF MEDICINAL ANIMALS IN THE FIRST JUZ OF THE ḤAYĀTU L-ḤAYAWĀN MANUSCRIPT BY SHAYKH KAMĀLU D-DĪN AD-DĀMIRĪ - Fatkhu Rohmatin; Istadiyantha (Institut Agama Islam Ngawi, 2021)
Abstract Indirectly, traditional medicine which is an ancestral heritage is a guide, a role map, and even a foundation for the continuity and development of medicine in the modern era. Therefore, the documentation and assessment of ancestral heritage with regard to traditional medicine, whether written in the form of artifacts, inscriptions, and manuscripts as well as those applied to the daily life culture of certain communities, is still a strategic area for study. This paper intends to describe the variety of medicinal animals contained in the Ḥayātu l-Ḥayawān manuscript (A-158). An encyclopedia of animals arranged alphabetically by Shaykh Kamālu d-Dīn ad-Damīrī and then summarized in various versions by scientists after him. The manuscript used as the object of this study is a summary version of Shaykh Ad-Damāmīnī with the title ‘Ainu l-Ḥayāt. The results of this study indicate that not all animals described in the first chapter of the Ḥayātu l-Ḥayawān manuscript are accompanied by an explanation of their efficacy. Meanwhile, the efficacy of the animals that dominates or is most commonly found is as an aphrodisiac or to increase sexual arousal. Keyword: Ḥayātu l-Ḥayawān, Medicinal animal, ‘Ainu l-Ḥayāt, Manuscript, ad-Damīrī